An Investigation On The Development Of Educators' Creative And Professional Capacities - Ying, Song; Vasudeva Panicker, Chandra Mohan (Journal of Neonatal Surgery, 2025)
In the recent decade, arts education has become an increasingly integral part of general education teacher preparation programs in the United States. However, there is a dearth of research on the ways in which educators prioritize the arts and use innovative pedagogies in the classroom. The majority of K-12 teachers polled in this scientific research placed a high value on the arts, but they seldom included them into their teaching, the results show. There is an excess of demands to learn all that is required, yet there is a dearth of chances to advance in one's career. Teachers' stated aims for incorporating art into the classroom were all over the place, ranging from promoting a greater understanding and respect for many cultures to inspiring pupils to be more engaged and enjoy themselves. The amount of time that teachers spent discussing the arts in class was inversely related to their self-confidence. Interestingly, instructors' interest in the arts, field experience, and creative activities had no impact on how they integrated the arts into their lessons.